"Beading Becomes a Part of Your Life": Transforming the Academy Through the Use of Beading as a Method of Inquiry. Issue 3 (November 2016) - Ray, Lana
Indigenous women's knowledge traditions remain largely marginalized within the academy to the detriment of Indigenous communities. The act of beading can serve to disrupt the dislocation of Indigenous women's ways of knowing, providing an avenue for Indigenous women to pursue research that is congruent with their worldviews and understandings of ethical and meaningful relationships. Drawing from the author's doctoral work, which was pursued as a beading project, this article outlines the use of beading as a method of inquiry. Through beading, which can be understood as a form of storytelling, a collective theoretical framework that fosters individuality within the context of relational accountability and nation building emerges. Also, the common supplies of sinew and beeswax used by Anishinaabe women in their beadwork support an Anishinaabecentric approach to research. This is reinforced by the process and aesthetic of beading, which generate the values of respect, balance, harmony centeredness, and repetition.